2014
DOI: 10.1017/s0958344014000214
|View full text |Cite
|
Sign up to set email alerts
|

Learning motivation and adaptive video caption filtering for EFL learners using handheld devices

Abstract: The aim of this study was to provide adaptive assistance to improve the listening comprehension of eleventh grade students. This study developed a video-based language learning system for handheld devices, using three levels of caption filtering adapted to student needs. Elementary level captioning excluded 220 English sight words (see Section 1 for definition), but provided captions and Chinese translations for the remaining words. Intermediate level excluded 1000 high frequency English words, but provided ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…These results are consistent with the findings in [19], which indicated positive support for the integration of technologies in English learning, as they provided students with more opportunities to use English and benefited their learning performance. Similarly, it agrees with the findings of [20] who used a video-based English learning system and their results indicated that students who learned with this approach practiced more English; in addition, their intrinsic motivation also improved more than that of those who learned with conventional video observation.…”
Section: Learning Variable Summarysupporting
confidence: 87%
“…These results are consistent with the findings in [19], which indicated positive support for the integration of technologies in English learning, as they provided students with more opportunities to use English and benefited their learning performance. Similarly, it agrees with the findings of [20] who used a video-based English learning system and their results indicated that students who learned with this approach practiced more English; in addition, their intrinsic motivation also improved more than that of those who learned with conventional video observation.…”
Section: Learning Variable Summarysupporting
confidence: 87%
“…Some researchers focused on the captions. The adaptive caption filtering approach proposed by Hsu [106] has proved that it may be an effective way to improve listening proficiency, because different students need different amounts of information to balance the listening comprehension. Hsu [107] found that the proportion of advanced words in writing was higher when watching video without captions than when watching video with captions before writing.…”
Section: Online Videomentioning
confidence: 99%
“…Student learning can be enhanced via a variety of apps, such as dictionaries, reading, writing, graphic organisers, note-taking, multimedia production, and communication. Within this framework of Mobile Assisted Language Learning (MALL), mobile technology can contribute to language development of vocabulary (Lin & Yu, 2017), grammar (Khodabandeh, Alian, & Soleimani, 2017), reading (Lin, 2014), listening (Hsu, 2015), speaking (Sun et al, 2017), and writing (Eubanks, Yeh, & Tseng, 2018). By embracing MALL, teachers demonstrate that they are keen to integrate mobile technology into their teaching (Hsu, 2016;Young, 2016).…”
Section: Ipads In Efl Classroomsmentioning
confidence: 99%